2016
DOI: 10.1155/2016/8651630
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Fault Diagnosis in a Power Distribution Network

Abstract: This paper presents a novel method of fault diagnosis by the use of fuzzy logic and neural network-based techniques for electric power fault detection, classification, and location in a power distribution network. A real network was used as a case study. The ten different types of line faults including single line-to-ground, line-to-line, double line-to-ground, and three-phase faults were investigated. The designed system has 89% accuracy for fault type identification. It also has 93% accuracy for fault locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Numerous research has also been conducted on the adoption of intelligent algorithms and machine learning methods for power fault detection and analysis. In [49], a proposal is made to detect faults using a Fuzzy Logic Controller (FLC) and to identify the fault location, Adaptive Neuro Fuzzy Inference System (ANFIS) is suggested. The study focused on how the distribution grid incidences can be detected, identified, and located.…”
Section: Figure 2 Main Components Of a Scada Systemmentioning
confidence: 99%
“…Numerous research has also been conducted on the adoption of intelligent algorithms and machine learning methods for power fault detection and analysis. In [49], a proposal is made to detect faults using a Fuzzy Logic Controller (FLC) and to identify the fault location, Adaptive Neuro Fuzzy Inference System (ANFIS) is suggested. The study focused on how the distribution grid incidences can be detected, identified, and located.…”
Section: Figure 2 Main Components Of a Scada Systemmentioning
confidence: 99%
“…Oluleke. babayomi et al [121] proposed and presented a fault identification and localization based on an adaptive neuro-fuzzy for the DSN. The fault data are collected from the network and are applied to train the fuzzy inference system to find out the location of the fault.…”
Section: Microgrids Fault Localization Challengesmentioning
confidence: 99%